ANALISIS KOMPARASI PERSEPSI KONSUMEN PENGGUNA OJEK ONLINE GO-RIDE DAN GRAB BIKE ( Studi kasus pada mahasiswa pengguna ojek Online Go-Ride dan Grab-Bike di UPN Veteran Jawa Timur) - Novia, Chuzaematin; Andarini, Sonja (Jurnal Bisnis Indonesia, 2019)
The  problem  in  this  study  is  that  there  are  differences  in  consumer perceptions of Go-ride and Grab-bike users. Consumers compare consumer perceptions in terms of brand image, risk and service quality. The purpose of this study was to determine the differences in consumer perceptions of Go-ride and Grab-bikes users as students at UPN “Veteran” East Java. Purposive sampling is a sampling technique in this study with the criteria (1) Active students at UPN “Veteran” East Java, (2) Students who have used Go-Ride and Grab-Bike at least 3 times in the past 6 months.. Data was obtained by distributing questionnaires to 100 respondents. The analysis technique used in this study is the Paired Sample T-test processed using SPSS 16.0 for windows. The results showed that: (1) the majority of Go-ride and Grab-bike consumer profiles as students of UPN "Veteran" East Java were women, with a monthly allowance of less than Rp 1,500,000, with the intensity of using Go-ride and Grab- bike 3-6 times in the last 6 months, (2) there are differences in consumer perceptions of brand image between Go-ride and Grab-bike which shows an average result that the Go-ride brand image is better than Grab-bike , (3) there are differences in consumer perceptions of the risk between Go-ride and Grab-bike which shows an average result that the Go-ride brand image is better than Grab-bike, (4) there are differences  in  consumer  perceptions  of  the service quality between  Go-ride  and Grab-bike which shows an average result that the Go-ride brand image is better than Grab-bike.   Keyword : consumer perceptions, brand image, risk and service quality